Pemberian McKenzie Exercises dan Infrared terhadap Penurunan Nyeri Punggung Bawah Miogenik pada Pegawai Poli Rehabilitas RSU Mitra Medika Tanjung Mulia - Heri Saputra; Riani Baiduri Siregar; Rudi Purwana (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Myogenic low back pain is a complaint of pain in the lower back area caused by disorders of muscle tissue or tendons, without nerve involvement. This complaint is often experienced by individuals who perform repetitive physical activities or maintain a hunched sitting position for long periods, resulting in muscle fatigue and discomfort. This study aims to analyze the effectiveness of McKenzie Exercise and infrared therapy in reducing myogenic low back pain. The study design used a one-group pre- and post-test with control design, with a total of 20 employees in the rehabilitation unit of RSU Medika Tanjung Mulia who had met the inclusion criteria. Subjects were randomly divided into two groups: Group I received McKenzie Exercise and infrared therapy interventions along with standard hospital therapy, while Group II only received standard hospital therapy. Pain levels were measured using a Numeric Rating Scale before and after the intervention. The results of statistical analysis showed a significant reduction in pain in both groups after the intervention, with a p value = 0.000 (p < 0.05). In addition, the results of the comparison between groups showed that the group receiving McKenzie Exercise and infrared therapy experienced a greater reduction in pain than the control group. This suggests that the combination of McKenzie Exercise and infrared therapy is more effective in reducing myogenic low back pain. This study recommends the use of both interventions as part of the physiotherapy management of low back pain caused by muscle disorders.